Poor performance status, urban residence and female sex predict inferior survival in pediatric advanced stage mature B-NHL in an Indian tertiary care center. (2nd January 2018) - Patel, Amol; Sharma, Meher Chand; Mallick, Saumyaranjan; Patel, Manali; Bakhshi, Sameer
ABSTRACT: Background : Advanced stage is a known prognostic factor in B-Non-Hodgkin Lymphoma (NHL); however, factors within advanced stage and overall data on pediatric B-NHL from India are lacking.Methods : This is a retrospective study wherein all consecutive pediatric (≤18 years) patients of advanced stage B-NHL (St. Jude stage 3 and 4) treated at our center from Jan 2003 to June 2016 with BFM-90 protocol were evaluated for outcome and pathology review.Results : Total 140 patients were analyzed with median age 8 years; M:F ratio was 5.2:1; 36% patients presented within 30 days of symptom onset and 58% had rural residence. Burkitt lymphoma (66%) was commonest histopathological subtype; bone marrow was involved in 15% and CSF in 8% cases. Undernourishment was observed in 30% patients and 51% had ECOG performance status of 3&4. At 5 years, EFS was 52 ± 4% (CI 0.43–0.60) and OS was 61 ± 4% (CI 0.52–0.68). On multivariate analysis, poor performance status ( p < 0.001) and urban residence ( p = 0.016) emerged as significant negative prognostic factors for EFS; while for OS, female sex ( p = 0.006), poor performance status ( p < 0.001) and urban residence ( p = 0.023) predicted inferior outcome.Conclusion : This is the largest study from south Asia on advanced stage pediatric B-NHL and it suggests undernourishment, poor performance status and gender bias to be unique features at presentation. Although, outcomes are comparable with other data from resource-challenged nations, yet they are 15–20% inferior than trial data from other developed countries. Further, poor performance status, female sex and urban residence for poor outcome were identified as unique prognostic factors.